Propagation dynamics on complex networks : models, methods and stability analysis - Fu, Xinchu (Wiley, 2014)
"Providing an introduction of general epidemic models, Propagation Dynamics on Complex Networks explores emerging topics of epidemic dynamics on complex networks, including theories, methods, and real-world applications with elementary and wide-coverage. This valuable text for researchers and students explores models evolving over complex networks and presents results concerning dynamics of Network-based models on a macroscopic scale. The text presents the fundamental knowledge needed to demonstrate how epidemic dynamical networks can be modeled, analyzed, and controlled along the state-of-the-art and recent progress in the field and related issues arising from various epidemic systems"--